2023
DOI: 10.1101/2023.02.01.23285346
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Influence of autozygosity on common disease risk across the phenotypic spectrum

Abstract: Autozygosity is associated with rare Mendelian disorders and clinically-relevant quantitative traits. We investigated associations between FROH(fraction of the genome in runs of homozygosity) and common diseases in Genes & Health (N=23,978 British South Asians), UK Biobank (N=397,184), and 23andMe, Inc. We show that restricting analysis to offspring of first cousins is an effective way of removing confounding due to social/environmental correlates of FROH. Within this group in G&H+UK Biobank, we found … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 65 publications
0
2
0
Order By: Relevance
“…From another study within this cohort, Malawsky et al (2023) 75 demonstrated that increased homozygosity (higher F ROH ) was associated with multiple common diseases. The primary hypothesis for these associations is that 30 homozygous regions of the genome contained causal variants with recessive effects on these phenotypes 76 .…”
mentioning
confidence: 76%
See 1 more Smart Citation
“…From another study within this cohort, Malawsky et al (2023) 75 demonstrated that increased homozygosity (higher F ROH ) was associated with multiple common diseases. The primary hypothesis for these associations is that 30 homozygous regions of the genome contained causal variants with recessive effects on these phenotypes 76 .…”
mentioning
confidence: 76%
“…A list of 237 custom phenotypes were compiled manually, and a second set of 1,281 phenotypes were defined based on International Classification of Disease (ICD10) codes. Further detail is described in Malawsky et al (2023) (Methods section on "Phenotypic data harmonisation and preparation for G&H") 18 . We retained phenotypes with ≥30 cases and also classified them into those that affected both sexes or were sex-specific (i.e.…”
Section: Phenotype Curationmentioning
confidence: 99%